2022
DOI: 10.1021/jacs.2c06662
|View full text |Cite
|
Sign up to set email alerts
|

A Borane Lewis Acid in the Secondary Coordination Sphere of a Ni(II) Imido Imparts Distinct C–H Activation Selectivity

Abstract: Two borane-functionalized bidentate phosphine ligands that vary in tether length have been prepared to examine cooperative metal−substrate interactions. Ni(0) complexes react with aryl azides at low temperatures to form structurally unusual κ 2 -(N,N)-N 3 Ar adducts. Warming these adducts affords products of N 2 extrusion and in one case, a Ni-imido compound that is capped by the appended borane. Reactions with 1-azidoadamantane (AdN 3 ) provide a distinct outcome, where a proposed nickel imido intermediate ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 92 publications
0
21
0
Order By: Relevance
“…Drover and co ‐workers demonstrated that the appended borane moiety has great impact on the ability of the hydride complexes [ B H] + in hydride transfer, as well as the oxidative addition behavior at the Ni 0 center in B [7] . Very recently, Chu, Szymczak and the co‐workers successfully applied a pendant 9‐BBN (borabicyclo[3.3.1]nonyl) group to stabilize the reactive Ni II imido intermediates (Ni=NR) thanks to the presence of the secondary B−N interactions ( C ), and thus achieved the intermolecular 1,2‐C Ar ‐H‐addition or intramolecular 1,2‐C benzylic ‐H‐addition across the Ni=N bonds [8] . It is noteworthy that the unique chemical behavior of the d ‐metal complexes bearing acidic groups in the secondary coordination sphere is commonly associated with the oxidative‐addition/reduction‐elimination process, [5d, 6, 7a,b, 8] which is nevertheless unfavorable for f ‐metals.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Drover and co ‐workers demonstrated that the appended borane moiety has great impact on the ability of the hydride complexes [ B H] + in hydride transfer, as well as the oxidative addition behavior at the Ni 0 center in B [7] . Very recently, Chu, Szymczak and the co‐workers successfully applied a pendant 9‐BBN (borabicyclo[3.3.1]nonyl) group to stabilize the reactive Ni II imido intermediates (Ni=NR) thanks to the presence of the secondary B−N interactions ( C ), and thus achieved the intermolecular 1,2‐C Ar ‐H‐addition or intramolecular 1,2‐C benzylic ‐H‐addition across the Ni=N bonds [8] . It is noteworthy that the unique chemical behavior of the d ‐metal complexes bearing acidic groups in the secondary coordination sphere is commonly associated with the oxidative‐addition/reduction‐elimination process, [5d, 6, 7a,b, 8] which is nevertheless unfavorable for f ‐metals.…”
Section: Figurementioning
confidence: 99%
“…Very recently, Chu, Szymczak and the co‐workers successfully applied a pendant 9‐BBN (borabicyclo[3.3.1]nonyl) group to stabilize the reactive Ni II imido intermediates (Ni=NR) thanks to the presence of the secondary B−N interactions ( C ), and thus achieved the intermolecular 1,2‐C Ar ‐H‐addition or intramolecular 1,2‐C benzylic ‐H‐addition across the Ni=N bonds [8] . It is noteworthy that the unique chemical behavior of the d ‐metal complexes bearing acidic groups in the secondary coordination sphere is commonly associated with the oxidative‐addition/reduction‐elimination process, [5d, 6, 7a,b, 8] which is nevertheless unfavorable for f ‐metals. As such, uranium complexes with appended borane moieties should exhibit distinctive reactivity profiles, which led us to focus on this class of compounds.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Furthermore, a role for such Lewis acidic SCSs has been exposed in iodoarene C-I bond oxidative addition using a [Ni(diphosphine)2] complex, and in producing divergent reaction pathways in the reaction of Ni(0) with organoazides. 8,9 Our group has contributed a number of diphosphine ligands where unsaturated R-groups serve as modifiable sites for the installation of Lewis-acids (boranes; -BR2) via hydroboration. 10,11,12,13 In most cases, installation is performed post-coordination, the success of which depends on the nature of metal starting material.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Very recently, Chu, Szymczak and the co‐workers successfully applied a pendant 9‐BBN (borabicyclo[3.3.1]nonyl) group to stabilize the reactive Ni II imido intermediates (Ni=NR) thanks to the presence of the secondary B−N interactions ( C ), and thus achieved the intermolecular 1,2‐C Ar ‐H‐addition or intramolecular 1,2‐C benzylic ‐H‐addition across the Ni=N bonds. [8] It is noteworthy that the unique chemical behavior of the d ‐metal complexes bearing acidic groups in the secondary coordination sphere is commonly associated with the oxidative‐addition/reduction‐elimination process,[ 5d , 6 , 7a , 7b , 8 ] which is nevertheless unfavorable for f ‐metals. As such, uranium complexes with appended borane moieties should exhibit distinctive reactivity profiles, which led us to focus on this class of compounds.…”
mentioning
confidence: 99%